The crystal structure of 6-(4-bromobenzyl)-1,3,5-trimethyl-7-phenyl-1,5-dihydro-2H-pyrrolo[3,2-d]pyrimidine-2,4(3H)-dione, C22H20BrN3O2 - Alexander Orbett T.; Donka Rajasekhar; Tonder Johannes H. van; Bezuidenhoudt Barend C.B.; Visser Hendrik G. (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C22H20BrN3O2, monoclinic, P21/c (no. 14), a = 15.889(12) Å, b = 16.332(13) Å, c = 7.324(5) Å, β = 94.985(5), V = 1893(2) Å3, Z = 4, Rgt(F) = 0.0295, wRref(F2) = 0.0790, T = 100(2) K.